2012
DOI: 10.1182/blood-2012-02-407999
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of bortezomib in myelodysplastic syndrome/acute myeloid leukemia depend on autophagy-mediated lysosomal degradation of TRAF6 and repression of PSMA1

Abstract: IntroductionMyelodysplastic syndrome (MDS) is a hematologic malignancy defined by blood cytopenias due to ineffective hematopoiesis, a predisposition to acute myeloid leukemia (AML), and genomic instability. 1,2 Molecular-targeted therapies do not exist for MDS and the mechanisms of current therapies are largely unknown. More recently, bortezomib (Velcade), which is widely used for the treatment of multiple myeloma (MM) and lymphomas, is being evaluated as a single agent or in combination with chemotherapy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 47 publications
(57 reference statements)
5
91
0
Order By: Relevance
“…Fang et al indicated that RNAi-mediated knockdown of TRAF6 sensitized both bortezomib-sensitive and -resistant cell lines, implying a key role for TRAF6 in bortezomib-induced cytotoxicity. Furthermore, reduced TRAF6 protein levels coincide with bortezomib-induced autophagy and subsequent apoptosis in myelodysplastic syndrome and acute myeloid leukemia [24]. In the current study, combined MG132 and IR treatment resulted in reduced TRAF6 protein and TAK1 phosphorylation levels (Fig.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Fang et al indicated that RNAi-mediated knockdown of TRAF6 sensitized both bortezomib-sensitive and -resistant cell lines, implying a key role for TRAF6 in bortezomib-induced cytotoxicity. Furthermore, reduced TRAF6 protein levels coincide with bortezomib-induced autophagy and subsequent apoptosis in myelodysplastic syndrome and acute myeloid leukemia [24]. In the current study, combined MG132 and IR treatment resulted in reduced TRAF6 protein and TAK1 phosphorylation levels (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…More recently, it was demonstrated that bortezomib (a proteasome inhibitor) induces proteasomeindependent degradation of the TRAF6 protein in myelodysplastic syndrome; such as acute myeloid leukemia cell lines and primary cells. Notably, TRAF6 is necessary for maintaining the survival of cells, and its degradation by bortezomib-induced autophagy contributes to cell death [24]. However, whether TRAF6 plays a critical role in the control of autophagy in pancreatic cancer cells remains undetermined.…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, BLOOD 23,24 During autophagy, the microtubule-associated protein 1 light chain 3 (LC3-I) is converted to membrane-bound LC3-II and specifically associates with autophagosomes. 25 Treatment of MV4-11 cell line and FLT3-ITD primary samples with bortezomib increased the number of autophagosomes, as indicated by the conversion of LC3-I to LC3-II ( Figure 3A-B).…”
Section: Bortezomib Activates Cytotoxic Autophagy In Aml Cellsmentioning
confidence: 99%
“…Moreover, knockdown of these specific miRNAs or overexpression of Traf6 in murine HSPC recapitulates the hematologic features of del(5q) MDS in a transplant model (10), providing convincing evidence that sustained TLR activation is a critical factor driving the malignant phenotype. More recent findings indicate that TRAF6 is essential for survival and proliferation of MDS HSPC (11) and sustained TLR activation skews their commitment toward the myeloid lineage while suppressing osteoblast differentiation (12,13), analogous to the senescence-dependent changes observed with normal aging (14).…”
Section: Introductionmentioning
confidence: 99%